Orthopantomogram as an Assessment Tool for Identifying Growth Pattern #x2013; A Radiographic Study (Global Journal of Medical Research, 2022)
Growth prediction is an estimation of alteration in speed and direction of growth. The ability to predict growth patterns of mandible, maxilla and other craniofacial structures plays an important role in improving the reliability of treatment planning and long term success of orthodontic patients. Bjork suggested structural signs such as inclination of condylar head, curvature of mandibular canal, shape of lower border of mandible, depth of antegonial notch, etc. to find the direction of mandibular growth. The purpose of the present study is to evaluate mandibular growth pattern using various Bjork structural signs on Orthopantomograms
Keywords: lateral cephalogram; OPG; mandibular curvature; gonial angle; inclination of condylar head and depth of antegonial notch